Transnational organised crime and translation, 2016-2018 - Drugan, Joanna (UK Data Service, 2021)
During the TOCAT project, we conducted multiple interviews and focus groups with frontline workers involved in police and related investigations across languages. Some of these were for information, to understand the experiences of interpreters in particular. These are included in this data collection. Others were designed for understanding by the UK police, Home Office and College of Policing, to inform internal training and guidance. Most of these were with practising investigators who required guarantees of confidentiality in order to discuss live investigations. These are therefore not included. In addition, many interpreters refused permission to share the data in their interviews due to their professional duty of client confidentiality. These are therefore also not included. Finally, some police and Home Office trainers were interviewed. Their interviews are not included as the number of trainers is very small and the individuals could be identified from their responses. The interviews included here were all qualitative semi-structured interviews conducted in person or by phone. All the interviews included here were conducted by the Principal Investigator, Prof. Joanna Drugan. They were transcribed by a team of trained transcribers and checked and anonymised by the PI prior to upload to remove any details which might identify individuals (e.g. the language spoken, as this is a very small specialised field in the UK where professionals are in close contact with one another). Our societies are more diverse than ever - more than 300 languages are spoken in the UK today. This increased diversity has had a major impact for the police. Officers now have to investigate and combat organised crime 'networks' whose members communicate across multiple languages. Police therefore increasingly need translators to be able to investigate serious crimes such as people trafficking and child sexual exploitation. This involves significant challenges, including cost, number of languages, quality and the limited supply of qualified linguists. In the Transnational Organised Crime and Translation (TOCAT) project, researchers, the police and translation providers worked together to understand and face up to these challenges. Our starting point was the need for practical guidance to help police officers and translators work together as effectively as possible. A working group drafted official new UK guidelines for police to use when they work with translators. The TOCAT project team conducted trials of these new guidelines, using a 'Test, Learn, Adapt' approach. Selected police officers and Home Office investigators in the UK and Belgium were trained to use the guidelines, then researchers interviewed and 'shadowed' officers as they worked to measure their effectiveness in practice, as well as any other potential needs identified by the users. This allowed us to revise the approach to make it better suited to actual needs. The Belgian trial also allowed us to test how far the approach could be 'translated' to other countries facing similar challenges, since transnational crime operates across national borders. The main questions we asked were: 1) How can police work more effectively to understand and fight transnational organised crime such as people trafficking when it is conducted across different languages? In particular, how should police work with translators when victims, witnesses or suspects don't speak the same language as investigators? 2) Is the planned police approach effective in practice, and, where it is not, what can be done to enhance it? And 3) What are the experiences of frontline workers (police officers, support workers, translators) when they face these new challenges, and can they help us develop a better overall understanding of transnational organised crime? To answer these questions, two researchers at the University of East Anglia in the UK, Prof Joanna Drugan and Dr Alexandria Innes, worked with two researchers at the University of Leuven in Belgium, Prof. Heidi Salaets and Dr Katalin Balogh. We drew on our established partnerships with the police and all the professional associations representing translators to design and carry out the research. The research team has decades of experience in researching translation practice in 'real-world' settings, migration, and police working with linguists, suspects and victims of crime, including children and other vulnerable groups. Prof Drugan, an expert in translation quality, oversaw the project. Prof Drugan and Dr Innes, who is an expert in migration, conducted the UK research, working with the Home Office, four different Constabularies and the College of Policing. Prof. Salaets and Dr Balogh, who both have expertise in interpreting in police settings, conducted the Belgian research, working with local and federal Police. We focused particularly on the crimes of human trafficking and smuggling in this project. We also focused on the impact of language challenges on frontline workers, notably police officers and translators. We shared our research findings and the tried-and-tested approach as widely as possible among police, translation providers and researchers, including making our (anonymised) data available for free via the UK Data Service, for those interviews for which we were able to secure permission. The result is a valuable contribution to evidence-based policing of increasingly significant transnational crimes, which can support further research on this important topic.